Answer:
The equation is:
![S=(a_n*r-a_1)/(r-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c595gwrtzo9d53eb5egv6f7e9y5yyqpgzc.png)
![S=((16)/(243)*(2)/(3)-(1)/(3))/((2)/(3)-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cdyfd3trr9rkbquzx60aqp3mjaa2iwvjil.png)
The sum is:
![S=(211)/(243)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nz8wx4t2bd9v8y3wubiul857gy9pkd0y4k.png)
--------------------------------------------------------------------
If the sequence is infinite, the formula is:
![S = (a_1)/(1-r)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8g0rb2ws0izhod5s43syuq2uaej13cmc4i.png)
-------------------------------------------------------------------
Explanation:
We must calculate the radius of the geometric series
![r =(a_(n+1))/(a_n)\\\\r=((2)/(9))/((1)/(3))\\\\r=(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cnrs4nog16hm39q37x4dxmckhygfem6a9j.png)
The first term of the series is:
![a_1=(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y2nizh7v7fl0e4v7rsdv8p35smguijl5cv.png)
The last term of the series is:
![a_n=(16)/(243)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ritfi3ecbmtxmk6wyuxg3sf5nlyko1lmyg.png)
If the sequence is finite then the formula is:
![S=(a_n*r-a_1)/(r-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c595gwrtzo9d53eb5egv6f7e9y5yyqpgzc.png)
![S=((16)/(243)*(2)/(3)-(1)/(3))/((2)/(3)-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cdyfd3trr9rkbquzx60aqp3mjaa2iwvjil.png)
![S=(211)/(243)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nz8wx4t2bd9v8y3wubiul857gy9pkd0y4k.png)
If the sequence is infinite then by definition as the radius are
then the formula for the sum of the geometric sequence is:
![S = (a_1)/(1-r)\\\\S = ((1)/(3))/(1-(2)/(3))\\\\S =1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k4ryijvj5kkovmwarntl3nfh1pega6r5xp.png)